High allele frequency of CYP2C9*3 (rs1057910) in a Negrito's subtribe population in Malaysia; Aboriginal people of Jahai. (2nd September 2016) - Rosdi, Rasmaizatul Akma; Mohd Yusoff, Narazah; Ismail, Rusli; Soo Choon, Tan; Saleem, Mohamed; Musa, Nurfadhlina; Yusoff, Surini
Abstract: Background : CYP2C9 gene polymorphisms modulate inter-individual variations in the human body's responses to various endogenous and exogenous drug substrates. To date, little is known about the CYP2C9 gene polymorphisms among the aboriginal populations of the world, including those in Malaysia. Aim : To characterise and compare the CYP2C9 polymorphisms ( CYP2C9*2, CYP2C9*3, CYP2C9*4 and CYP2C9*5 ) between one of Malaysia's aboriginal populations, Jahai, with the national major ethnic, Malay. To also compare the allele frequencies from these two populations with available data of other aboriginal populations around the world. Subjects and methods : The extracted DNA of 155 Jahais and 183 Malays was genotyped for CYP2C9 polymorphisms using a nested multiplex allele-specific polymerase chain reaction technique. The results were confirmed by DNA direct sequencing. Results : Genotyping results revealed that CYP2C9*2, CYP2C9*4 and CYP2C9*5 were absent in Jahais, while only the latter two were absent in Malays. The CYP2C9*3 allelic frequency in Jahais was 36.2%, making them the most frequent carriers of the allele thus far reported in any ethnic group from Southeast Asia. Conclusions : The high frequency of CYP2C9*3 and the absence of CYP2C9*2 in Jahais suggest that genetic drift may be occurring in this ethnic group. This is the first study to determine the CYP2C9 polymorphisms in an aboriginal population in Malaysia.